Analysis of self-esteem and self-efficacy levels of music students - OTACIOĞLU, SERKAN (My University, 2020)
The main aim of this study is to determine whether professional music education has any effect on “self-esteem” and “self-efficacy” of undergraduate students who study at different universities. The study was carried out with 55 students who study at Marmara University Atatürk Faculty of Education Department of Music Education and Istanbul University State Conservatory. Self-esteem level of students was measured with Self-Esteem Scale (RSE) which was developed by Rosenberg in 1965; selfefficacy levels were measured with Self-Efficacy Scale (SES) which was developed by Sherer et al. in 1982. The results showed that there were some statistically significant differences between RSE levels of students and some variables. Key words: Music education, self- esteem, self-efficacy.
Keywords: Music education; self- esteem; self-efficacy